Synergies Between Trade in Environmental Services and Trade in Environmental Goods - Steenblik, Ronald (OECD Trade and Environment Working Papers, 2005)
This paper examines the synergistic relationships between trade in environmental services and trade in environmental goods. It forms part of a series of OECD studies that analyse various issues related to Paragraph 31(iii) of the World Trade Organization's 2001 Doha Development Agenda, which mandates negotiations at the WTO on "the reduction or, as appropriate, elimination of tariff and non-tariff barriers to environmental goods and services." For the purpose of this study, environmental services are defined as wastewater management services, solid-waste management services, sanitation and similar services and other environmental services. Services related to the collection, purification and distribution of water are also discussed in the paper.